BINOMIAL DISTRIBUTION SERIES CONNECTED WITH CERTAIN SUBCLASSES OF ANALYTIC FUNCTIONS - et al., S.Santhiya (International Journal of Advanced Science and Technology, 2019)
The purpose of present paper is to obtain the necessary and sufficient conditions and inclusion relations for Binomial distribution series belonging to the subclasses and of analytic functions with negative coefficients. Further the integral operator is related to this series is also considered. 2010 Mathematics Subject Classiﬁcation: 30C45, 30C55.